Adonis : the art magazine of the male physique. (London London : Weider Publications Male Classics, 1955)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : 60 Greek Street, London W1; vanaf (1959) : Male Classics, 6-10 Lexington Street, London W1
Engels
Periodiek